ANALISIS DESKRIPTIF PENGARUH PERMAINAN EGRANG BATOK TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI - Laura Sayidina; Heri Yusuf Muslihin; Dwi Alia (STKIP Subang, 2025)
This research aims to describe the influence of the traditional game Egrang Batok on the gross motor development of children aged 4-5 years at TK Kartika IX-10 C. The background of this study is based on the low gross motor skills of children in terms of balance, coordination, and muscle strength, which are evident when children engage in physical activities such as walking straight, jumping, or throwing. Traditional games, especially Egrang Batok, are considered an enjoyable and effective medium for learning to stimulate children's gross motor development. The method used in this research is qualitative descriptive. Data collection techniques were carried out through direct observation of children's activities while playing Egrang Batok, documentation, and interviews with class teachers. The research results indicate that the traditional game Egrang Batok has a positive effect on the gross motor development of children. Children appear to be more balanced in walking, more confident in moving, and able to coordinate their hand and foot movements better. In addition, this game also increases children's participation in group activities and strengthens their social skills. In other words, the Egrang Batok game not only trains physical aspects but also supports the formation of children's character. Based on these findings, it is recommended that early childhood educators integrate traditional games like Egrang Batok into daily learning activities to optimally support gross motor development and instill local cultural values from an early age.